Frequent basal cell cancer development is a clinical marker for inherited cancer susceptibility - Cho, Hyunje G. (JCI Insight, 2018)
Innate DNA repair mechanisms play a critical role in protecting skin keratinocytes from UV mutagenesis and skin cancer development. We hypothesized that individuals who develop frequent skin cancers may harbor germline defects in DNA repair genes and have increased predisposition to internal malignancies. We enrolled 61 patients with unusually frequent basal cell carcinoma (BCC) development, seen at Stanford Hospital and Clinics from January 2005 until December 2015, for germline analysis of 29 DNA repair genes. In parallel, a case-control retrospective review was performed to interrogate the association of malignancies with frequent BCC development in a large US medical insurance claims database (Truven), which included 13,264 individuals with 6 or more BCCs from 2007 to 2011. 19.7% of the frequent BCC cohort harbored pathogenic mutations in DNA repair genes: APC, BARD1, BRCA1, BRCA2, CDH1, CHEK2, MLH1, MSH2, MSH6, MUTYH, NBN, and PALB2. Individuals with 6 or more BCCs had an increased risk of other malignancies, with a 3.5-fold increase in the frequent BCC cohort and a 3.2-fold increase in the Truven database. Individuals who developed frequent BCCs have an increased prevalence of germline mutations in DNA repair genes and increased malignancy risk. Our data implicate frequent BCC development as an external marker of inherited cancer risk.